Epidemiological analysis of turner syndrome in children aged 0–14 years: global, regional, and national perspectives (1990-2021) - Ding, Fang; Xu, Jiaoli; Xiong, Jingxuan; Li, Qinhong; Cheng, Zugen; Deng, Lili (Frontiers in Endocrinology, 2025)
BackgroundTurner syndrome (TS), a chromosomal disorder (45, X) affecting approximately 1 in 2,000 female births, results in multisystem morbidity. This study aims to report global trends in the prevalence and disability-adjusted life years (DALYs) of childhood TS from 1990 to 2021.MethodsThis study analyzed the prevalence and DALYs of TS in children aged 0–14 years using data from the Global Burden of Disease (GBD) database. Prevalence and DALYs were calculated per 100,000 population with 95% uncertainty intervals (UI). A log-transformed linear regression model was applied to estimate the average annual percentage change (EAPC) and evaluate temporal trends.FindingsGlobally, the prevalence of TS in children in 2021 was 240598.45 cases (95% UI, 185491.24,318611.47), with 174,186.30 DALYs (95% UI, 127,104.64–223,265.92). From 1990 to 2021, the prevalence increased by 12.81% (95% UI, 11.37% to 14.05%), and DALYs decreased by 66.13% (95% UI, -79.97% to -44.24%). Among the five Sociodemographic Index (SDI) regions, the highest EAPCs were observed in the High SDI regions for prevalence (0.03; 95% CI, 0.01–0.05) and DALYs (0.03; 95% CI, 0.01–0.05). Regionally, the largest decline in prevalence rate occurred in Andean Latin America (EAPC = –0.44; 95% CI, –0.45 to –0.43), and the greatest increase was recorded in the Caribbean (EAPC = 0.05; 95% CI, 0.00–0.10). At the national level, India had the highest number of TS cases in 2021, with 45,941.86 cases (95% UI, 35,104.78–61,429.72).InterpretationOverall, these findings provide a critical foundation for shaping public health strategies and policy decisions aimed at reducing the global burden of pediatric TS through improved diagnostic practices, comprehensive care, and targeted interventions.